THE INFLUENCE OF LEARNING INTEREST AND SELF-DISCIPLINE ON ENGLISH LEARNING ACHIEVEMENT (CASE STUDY ACADEMY OF ADMINISTRATIVE MANAGEMENT STUDENTS) - Andhina Ika Sunardi; Nafisatul Lutfi; Herman Wahyu Dwi Maelana (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the effect of interest in learning and self-discipline on English learning achievement of second semester students of the Yogyakarta Administrative Management Academy (AMAYO). Research hypotheses: 1) It is suspected that there is a significant effect of interest in learning on learning achievement in English. 2) it is suspected that there is a significant effect of self-discipline on learning achievement in English. 3) it is suspected that there is a significant influence of interest in learning and self-discipline simultaneously on achievement in learning English. The research was conducted by survey method. The population is second semester AMAYO students for the 2021/2022 academic year with a sample size of 77 students. By testing using multiple linear regression techniques. The results of hypothesis testing obtained the following conclusions: 1) There is a significant effect of interest in learning on English learning achievement of AMAYO students, that tcount (5.426) > ttable (1.6654); 2) There is a significant effect of self-discipline on English learning achievement of AMAYO students, that tcount (5,633) > ttable (1,6654); and 3) There is a significant effect of simultaneous interest in learning and self-discipline on AMAYO students' learning achievement in English, that Fcount (82,125) > ftable (3.158). The regression equation obtained is as follows Y = 2,935 + 0,579X1 + 0,627X2.